Stability Investigation of an AC-DC Power System Feeding a Buck Converter Controlled by Sliding Mode Controller - Surabadin Daengdon; Apichai Suyapan; Kongpan Areerak; Jakkrit Pakdeeto (IEEE Access, 2025)
Power converters are a highly important technology for power systems in electric vehicles (EVs), as well as in the generation and utilization of renewable energy. However, controlled power converters behave as constant power loads which directly affect the stability of the system. Therefore, this article presents stability investigation of an AC-DC power system feeding a buck converter controlled by a sliding mode controller. The stability analysis is conducted using the eigenvalue theorem and based on a system mathematical model derived through a combination of the DQ and the generalized state-space averaging methods. The theoretical analysis is verified through simulation on MATLAB/SIMULINK, hardware-in-the-loop (HIL), and experimental testing. The results demonstrate that the considered system exhibits instability due to the constant power load effect, which aligns with the theoretical predictions. In addition, the variation of DC-link filter parameters directly impacts the system stability. The resulting results provide useful insights for avoiding system operation at the unstable point and for designing the filter when the system stability is considered. Furthermore, this study serves as a foundation for future research.